Pengaruh Struktur Kepemilikan, Beban Pajak Tangguhan, Dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Riska Dwi Utami (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze how ownership structure, deferred tax expense, and firm size affect tax aggressiveness in Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange. The research method used is a quantitative approach with panel data regression techniques, and the type of data used is secondary data. In this study, to obtain samples that meet specific criteria, the purposive sampling method was applied. The population consists of 132 companies, and 8 sample companies were obtained, resulting in 48 research observations over a six-year period from 2019 to 2024. The results of the study show that, partially, ownership structure has no effect on tax aggressiveness, deferred tax expense has no effect on tax aggressiveness, firm size has an effect on tax aggressiveness, and simultaneously, ownership structure, deferred tax expense, and firm size have an effect on tax aggressiveness.